The heist [compact disc, unabridged] - Evanovich, Janet; Goldberg, Lee, 1962- (Evanovich, Janet. Fox and O'Hare novels., 2013)
FBI Special Agent Kate O'Hare is known for her fierce dedication and discipline on the job, chasing down the world's most wanted criminals and putting them behind bars. Her boss thinks she is tenacious and ambitious; her friends think she is tough, stubborn, and maybe even a bit obsessed. And while Kate has made quite a name for herself for the past five years, the only name she's cared about is Nicolas Fox, an international crook she wants in more ways than one.